SDM-MOOC: Artifact-Based Social Learning for 21st Century Skills - Wati, Qoriah Rahma; hidayat, sholeh hidayat (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study develops the Social-Distributed Micro-MOOC (SDM-MOOC), a digital learning approach that emphasizes social interaction, the use of thinking artifacts, and guided reflection to deepen learners’ conceptual understanding. The model was designed through theoretical review, needs analysis, and an initial pilot involving participants familiar with digital learning platforms. Data were collected from digital artifacts, collaborative conversations, and reflective notes, and were analyzed using qualitative content analysis techniques.The findings indicate that the SDM-MOOC framework is capable of fostering a learning ecosystem that makes thinking processes visible, sustains meaningful dialogue, and enables learners to reorganize their understanding through structured reflection. Participants demonstrated cognitive growth through a sequence of activities including stimulus engagement, artifact creation, collaborative discussion, and reflection. These results highlight that even simple digital platforms can serve as effective spaces for collaboration and knowledge construction when supported by appropriate pedagogical design.This study provides both conceptual and practical foundations for implementing socially oriented microlearning. The SDM-MOOC model holds potential for use across diverse educational settings and opens avenues for further research exploring artifact quality, discussion dynamics, and the relationship between distributed learning processes and learners’ conceptual development